Composite guidance laws using higher order sliding mode differentiator and disturbance observer. (November 2015) - He, Shaoming; Wang, Jiang; Lin, Defu
This paper has proposed a new composite robust guidance law to intercept maneuvering targets without line-of-sight (LOS) angular rate information. The presented guidance law is constructed through a combination of second-order sliding mode, higher-order sliding mode (HOSM) differentiator, and finite-time convergent disturbance observer (FTDOB). More specifically, the HOSM differentiator is used to extract the LOS angular rate information from LOS angle measurement, while the FTDOB is used to estimate and compensate the unknown target maneuvers. The finite-time stability of the closed-loop guidance system is established using finite-time bounded function and Lyapunov function methods. Next, the proposed guidance law is applied to three-dimensional homing engagement, where the FTDOB is used to estimate the target maneuver as well as the cross-coupling terms between the elevation and the azimuth motions. Numerical simulations with some comparisons are carried out to demonstrate the superiority of the proposed method.